Knowledge, attitude and practice of mothers/caregivers on infant and young child feeding in Shabelle zone, Somali Region, Eastern Ethiopia: A cross sectional study - Abdi Guled, Rashid; Mamat, Nik Mazlan; Mohd Abu Bakar, Wan Azdie; Assefa, Nega; Balachew, Tefera (Kulliyyah of Science, International Islamic University Malaysia, 2016)
Knowledge, attitude and practice (KAP) of mothers/caregivers on infant and young child feeding are key factors for optimal nutritional status, health and growth of the children. Hence, this study aims to assess the knowledge, attitude and practice of the mothers/caregivers on infant and young child feeding. A cross sectional study was carried out among 415 mothers/caregivers from Gode and Adadle Districts in Shabelle Zone of Somali Region, Eastern Ethiopia, by using semi structured interviewer administered questionnaire. The principal component analysis was carried out to generate KAP indices. Multivariable logistic regression analyses were performed to isolate independent predictors for good knowledge, good practice and favourable attitude of the mothers/caregivers related to child feeding. Out of 415 study participants, 87.5%, and 69.4% were illiterate, and from rural residence, respectively. The majority (96.1 %) of the participants knew the importance of colostrums, time initiation, exclusive and duration of the breastfeeding, and, 82% believed that a newborn should be given butter, sugar and water for the first six months. Furthermore, 50% of the mothers started breastfeeding within one hour after delivery, 66% of the participants started additional food items before the age of the six months, and 69.2% continued breastfeeding for 24 months and above. On multivariable logistic regression, after adjusting for other predictors, being in Gode District (P <0.001), and not being housewife (P = 0.014) were significantly associated with having good Knowledge about optimal infant and young child feeding (IYCF), and wealth index (P = 0.001) are positively associated with favourable attitude, and being literate (P = 0.01) is positively associated with good practice. Conversely, good knowledge about optimal IYCF were negatively associated with favourable attitude (P <0.001), and urban and semi urban residence was negatively associated with good knowledge (P <0.001). In conclusion, the findings showed that despite the high knowledge of the participants on IYCF; a large proportion of mothers/caregivers had negative attitude and poor practice on proper IYCF leading to high rate of suboptimal feeding practices. Behavior change communication interventions using strategies appropriate for the pastoralist and agro pastoralist community. That is, targeting on culture, believes and practices related to IYCF, need to be performed using religious leaders, teachers, students, youth associations, female associations, health professionals, frontline health actors, and developmental armies to bridge the gap between knowledge and practice.